Integrating Social and Business Case Approaches to Implement Watershed Development Projects in India - Kalra, B. S.; Mishra, Anil Kumar (Prabandhan: Indian Journal of Management, 2015)
In India, the rainfed agricultural areas, not necessary the water deficient ones, offer untapped potential for enhanced food production and food security. However, the policies adopted for rainwater harvesting in these areas have not integrated the private interests of the watershed community with public investment, and the farmers, at most of the times, remain aloof of such efforts. Strong access to tangible and direct benefits from rainwater harvesting measures and the opportunities for the watershed communities to contribute to such efforts are the prime requirements of the watershed development programmes. A support system for remunerative agriculture based on business principles needs to be a part and parcel of such efforts. Looking at the socioeconomic profile of the farmers in the rainfed regions, there is a need to create enabling institutional arrangements for them to become a part of it for effective implementation of watershed development projects. An autonomous two-tier village development society has been suggested for active participation of the local community and effective implementations of the projects. A closed chain business model is suggested to develop local partnerships for value addition and other business activities. However, institutional innovations have to be a continuous process which need to be experimented with to evolve an efficient and functional institution at the grass root levels.